The impact of Covid-19 on harm reduction policies in Iran: an interrupted time series analysis - Siavash Beiranvand; Meysam Behzadifar; Aidin Aryankhesal; Seyed Jafar Ehsanzadeh; Masoud Behzadifar (Harm Reduction Journal)
Abstract Background The global emergence of the Covid-19 pandemic in 2019 posed unprecedented challenges to healthcare systems, disrupting routine services and necessitating swift adaptations. Harm reduction programs, vital for addressing substance use-related health risks, faced unique challenges during the pandemic, impacting vulnerable populations. This study focuses on the repercussions of Covid-19 on harm reduction policies in Iran, specifically examining the distribution of condoms, syringes, and methadone to high-risk individuals attending Triangle Centers. Aim The study aims to assess the impact of the Covid-19 pandemic on harm reduction services in Iran and provide evidence-based insights for policy adjustments. Using Interrupted Time Series Analysis (ITSA), the research analyzes trends in the distribution of condoms, syringes, and methadone before and after the official declaration of the pandemic in February 2020. Method ITSA, a valuable tool for evaluating program impacts, was employed to analyze data collected from Triangle Centers in Lorestan Province, Iran. Monthly records of harm reduction services (condoms, syringes, methadone) from January 2017 to February 2023 were extracted. The pre-intervention period spanned January 2017 to January 2020, with the post-intervention period extending from February 2020 to February 2023. Statistical analyses were conducted using the Newey-West technique, Combi-Huizinga autocorrelation test, and Ordinary Least Squares (OLS) regression, with a significance threshold set at P-value < 0.05. Results Following the onset of Covid-19, the level change in condom distribution to high-risk individuals showed a significant decline, decreasing by 2,168.87 units per month (95% CI: -2,405.57 to -1,932.15). Methadone dispensation, crucial for opioid harm reduction, also witnessed a substantial level change, decreasing by 5,007.60 cc per month (95% CI: -6,251.75 to -3,763.45). Additionally, the provision of syringes decreased significantly, with a level change of -601.01 units per month (95% CI: -706.39 to -495.62). Conclusion This study reveals significant disruptions in harm reduction services in Iran post-Covid-19, emphasizing the need for targeted interventions. Factors such as fear, stigma, resource reallocation, and logistical challenges contribute to the observed decreases. Policymakers must prioritize sustaining harm reduction services during pandemics, ensuring continuity for vulnerable populations. The findings underscore the importance of proactive policy development and preparedness to prevent delays and inequalities in accessing essential services for individuals with high-risk behaviors. Overall, integrating harm reduction into pandemic planning is crucial for a resilient and equitable health system.